Oral health-related quality of life in Northland Māori children and adolescents with Polynesian amelogenesis imperfecta - Martin, Michelle; Gowda, Sunitha; Foster Page, Lyndie; Thomson, W. Murray (Frontiers in Dental Medicine, 2024)
Amelogenesis Imperfecta (AI) is a hereditary developmental disorder of tooth enamel with few known variants with differing characteristics, depending on where in the amelogenesis process an error has occurred. Polynesian AI (or Poly AI) is prevalent among people of Polynesian descent and is prevalent among New Zealand Māori. While the impact of AI on the quality of life has been reported in some studies, however, the role of Poly AI on oral health-related quality of life (OHRQoL) is not known. This study explores OHRQoL among New Zealand Māori with and without AI. A cross-sectional study was undertaken, with ethical approval obtained from the New Zealand Health and Disability Ethics Committee. 30 Māori children and adolescents with Poly AI and 60 Māori children and adolescents with no Poly AI as the comparison group matched by age and sex, were randomly selected and recruited participated in the study. OHRQoL was measured using the 19-item COHIP-SF. Statistically significant differences were observed in the OHRQoL between those with Poly AI and the comparison group. Linear regression analyses controlling for age and deprivation showed significantly poorer OHRQoL among those with Poly AI than in those with no Poly AI. The study findings highlight poorer OHRQoL among Māori children with Poly AI, emphasizing the need for early detection and management of the condition and the importance of providing appropriate training in diagnosing Poly AI and managing hypersensitivity. Further research among Polynesian populations is needed to understand the impact OHRQoL among those with Poly AI.